2016
DOI: 10.22146/jsp.15688
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor yang Mempengaruhi Kualitas Kinerja Kantor Pertanahan Rote Ndao

Abstract: The aim of this research is to analysis the influence of determinant (input) and process factors toward the performance (output) quality of Land Agency in Rote Ndao Regency. Variables used in this study are six independent variables and one dependent variable. The six independent variables are human resources supply, budget supply, facilities supply, infrastructure supply, bureaucracy efficiency and work dicipline, whereas the dependent variable is performance quality. The population of this study consists of 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Performance is the result of work that employees can achieve individually and in groups within an organization (Busro, 2018). Performance is the process of carrying out work and the results achieved for organizational goals (Sayd et al, 2016). Franceschini et al (2019) explained that performance measurement continuously monitors and reports program achievements, especially progress toward predetermined goals.…”
Section: B Literature Reviewmentioning
confidence: 99%
“…Performance is the result of work that employees can achieve individually and in groups within an organization (Busro, 2018). Performance is the process of carrying out work and the results achieved for organizational goals (Sayd et al, 2016). Franceschini et al (2019) explained that performance measurement continuously monitors and reports program achievements, especially progress toward predetermined goals.…”
Section: B Literature Reviewmentioning
confidence: 99%
“…Research that has been carried out related to the implementation of Permenkes NO 46 of 2015 has been examined by (Susilawati Susilawati, 2017) (Koesoemahardja et al, 2016) from the above research it can be concluded that Puskesmas need to deliver safe and quality services in order to realize development. Research that has been done related to the performance of human resources, especially in the health and pharmaceutical fields, has been studied by (Auliani, 2012) Ardianto ( 2012), (Suryanegara, 2013), (Sayd, 2014) and (Salamate, 2014). The result of the research above is that the performance of a public health facility, including both in pharmacies and pharmacy installations, is strongly influenced by the human resources working at the health facility.…”
Section: Introductionmentioning
confidence: 99%